Brokers courting voters: the alliance system in a rural Philippine village - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2018)
In lieu of the market model of vote buying, this study probes how brokers do their work of securing votes and what meanings people attach to the giving and receiving of money during elections. Based on an ethnography of a rural village in Camarines Sur province during the 9 May 2016 election campaign period, this study points to the strategic importance of ad hoc alliance systems that are not necessarily aligned with formal party structures. Created to promote a local candidate, an alliance network relies on village brokers, who engage in personalized communication strategies to convince voters to support specific candidates. However, competing alliance networks create deep social fractures. Amid social tensions, brokers establish relationships with voters in the context of which money is given not in exchange for a vote but as a reward for joining an alliance. Voters, for their part, regard money from their own moral perspectives. This study advances a cultural model of alliance systems in which broker agency, voter agency, and social relationships play key roles.